Improved responsiveness to change in joint space width over 24-month follow-up: comparison of 3D JSW on weight-bearing CT vs 2D JSW on radiographs in the MOST study. Issue 3 (March 2023) - Segal, N.A.; Nevitt, M.C.; Morales Aquino, M.; McFadden, E.; Ho, M.; Duryea, J.; Tolstykh, I.; Cheng, H.; He, J.; Lynch, J.A.; Felson, D.T.; Anderson, D.D.
Summary: Objective: Radiographic joint space width (JSW) has been a standard for measuring knee osteoarthritis (OA) structural change. Limitations in the responsiveness of this approach might be overcome by instead measuring 3D JSW on weight-bearing CT (WBCT). This study compared the responsiveness of 3D JSW measurements using WBCT with the responsiveness of radiographic 2D JSW. Design: Standing, fixed-flexion knee radiographs (XR) and WBCT were acquired ancillary to the 144- and 168-month Multicenter Osteoarthritis Study visits. Tibiofemoral JSW was measured on both XR and WBCT. Responsiveness to change was defined by the standardized response mean (SRM) for change in JSW (1) at predetermined mediolateral locations (JSWx) on both modalities and (2) in the following subregions measured on WBCT images: central medial and lateral femur (CMF/CLF) and tibia (CMT/CLT), and anterior and posterior tibia (AMT/ALT, PMT/MLT). Results: Baseline and 24-month follow-up JSWx measurements were completed for 265 participants (58.1% women). Responsiveness of 3D JSWx for medial tibiofemoral compartment on coronal WBCT (SRM range: −0.18, −0.24) exceeded that for 2D JSWx (−0.10, −0.16). Responsiveness of 3D JSW subregional mean (−0.06, −0.36) and maximal (−1.14, −1.75) CMF and CMT and maximal CLF/CLT 3D JSW changes were statistically significantly greater in comparison with respective medial and lateral 2D JSWx ( P ≤ 0.002). Conclusions: Subregional 3D JSW on WBCT is substantially more responsive to 24-month changes in tibiofemoral joint structure compared to radiographic measurements. Use of subregional 3D JSW on WBCT could enable improved detection of OA structural progression over a 24-month duration in comparison with measurements made on XR.